Strategi pengelolaan wisata alam berkelanjutan Sungai Gagak di Kabupaten Kampar - Lisa Fitriyani Simatupang; Ridwan Manda Putra; Viktor Amrifo (Pelantar Press, 2023)
Koto Mesjid Village is one of the tourist villages in Riau Province that has one of the natural attractions, the Gagak River. However, at present, it is known that the number of tourists visiting the Gagak River is decreasing, due to the increasingly poor infrastructure in the area. To conduct sustainable management of nature tourism from ecological, economic and social aspects so that it can be utilized for current and future generations, it is necessary to conduct research to determine the existing conditions of Gagak River and formulate appropriate management strategies for natural tourism of Gagak River. Data collection methods in the research consisted of field studies and document studies. Data analysis techniques consist of descriptive analysis and MDS analysis with Raptourism software. The results showed that the level of multidimensional sustainability was categorized as moderately sustainable (61.39%). Based on the results of the study, it is known that the ecological dimension is very sustainable, the social dimension is quite sustainable and the economic dimension is less sustainable. Sustainable management strategies for natural tourism of Gagak River to increase the value of sustainability can be done by: (1) Improving accessibility, (2) Developing tourism potential around the river, (3) Implementing local wisdom values as an effort to preserve the environment, (4) Increasing the capacity of managers to improve performance and ability in managing tourist attractions, and (5) Maintaining good relationship patterns to optimize institutional functions.